PEMBENTUKAN KOMPETENSI PRIBADI-SOSIAL MENURUT ALFRED ADLER DAN RELEVANSINYA DALAM BIMBINGAN DAN KONSELING PRIBADI-SOSIAL - Mufrihah, Arina (AL-TAZKIAH, 2013)
One area of guidance and counseling services are personal-social counseling. Forms of personal-social services in schools in general have a lot we find in some references. Therefore in this article suggests a form other than the personal social services in general, specifically the authors also propose forms of personal-social counseling services from the perspective of Alfred Adler, because the theory of individual psychology Adler in a great deal about personal and social competence, where a kegiataan humanity each individual views of the development of social concerns. Here the authors see that in giving personal-social counseling services, an alternative that can be used is the Adler thinking about a personal relationship with a healthy sense of social sensitivity owned, that social care is a benchmark in assessing the whole person. Departing from the concept, the authors look at how the formation of personal and social competence according to Adler, Adler thought relevance with personal-social counseling, and an implementation of Adlerian-School Counseling in schools that tend to drive the adaptive behavior of students in order to meet their needsand help students develop skills socializing in the school environment.